From tropical coral reefs to high latitude coral communities: insights into population dynamics along environmental gradients - Chong, Fiona (2025)
Anthropogenic climate change affects coral communities globally, exposing them to increasingly frequent disturbances. Thermal stress events might differentially compromise the recovery capacity of coral taxa across biogeographic scales. While changes in total coral cover are used extensively to monitor the status of many tropical coral reefs, relatively little information is available on high latitude coral communities, yet understanding population structure is essential for the forecasting of population dynamics under climate change. This thesis links size-based demographic approaches and coral-symbiont genetics to further our understanding of ecological processes affecting coral communities in biogeographic transition zones. The population size structure (or size spectra) of communities encompasses valuable information on the vital rates of populations. I explored how the population size structure of coral communities change along an approximately 900 km environmental gradient on the east coast of Australia, from the warmer and brighter southern Great Barrier Reef to the colder and more turbid rocky reefs of northern New South Wales. I found that there were fewer but bigger corals in the high latitude marginal reefs, implying that population persistence is reliant on fundamentally different demographic strategies along the gradient. Using compositional functional regression, I predicted the effect of increasingly marginal environments on entire coral size distributions. I further explored size spectra of fishes as well as corals along this environmental gradient, challenging the widespread assumption that the size-abundance relationship in ecological communities followed a (bounded) power law relationship. I also considered the common, but rarely-addressed issue of minus-sampling using photo-quadrats. I found that log-normal distributions might provide a better description to ecological size spectra, especially at the upper tails of the distribution. Finally, to understand the identity of coral taxa behind observed demographic differences along environmental gradients, I explored the genetic diversity of the Pocillopora species complex, and their Symbiodiniaceae endosymbiont community along a 1000 km environmental gradient in Japan. I found that high latitude corals are low in diversity and genetically distinct from their tropical congeners. This finding challenges the extent of tropicalisation in marine environments under climate change, with respect to sessile organisms such as corals. Overall, this thesis sought to improve our understanding of demographic processes in coral communities across biogeographic transition zones. Using a combination of high-quality size abundance and genetic data, I highlight fundamental differences in tropical coral reefs and their high latitude counterparts. I use and present methods that incrementally improve our ability to describe and model ecological size spectra, which has wider conservation and management applications. As climate change continues to affect communities worldwide, quantitative demographic approaches such as those presented in this thesis will continue to shape our ability to capture and predict population viability and persistence.
Keywords: Biological sciences